1995
DOI: 10.1515/cclm.1995.33.11.799
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and Complement C3 Polymorphism and Their Role in the Response to Gemfibrozil and Low Fat Low Cholesterol Therapy

Abstract: Summary:Three different allelic variants of apolipoprotein E determine, in concert with other gene products, the levels of plasma lipoproteins. Recently, cleavage products of the complement C3 molecule have also been implicated in determining plasma triacylglycerol concentrations.This study presents data of an ongoing study to dissect the role of the apolipoprotein E gene locus in the response to low fat/low cholesterol diet combined with gemfibrozil treatment. In addition, for the first time, the significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…For example, studies of cholesterol-lowering drugs, the hydroxymethylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, conducted in fairly large populations with specific clinical endpoints (beyond lipid changes), have focused on genetic polymorphisms in proteins not directly involved in the pharmacologic mechanism of the drug, namely apolipoprotein E (APOE), cholesteryl ester transfer protein (CETP), stromelysin-1 and β-fibrinogen. [64][65][66]68,69,72] These studies and their results have been strikingly consistent. Firstly, they investigated a genetic polymorphism thought or documented to be associated with an adverse clinical outcome (e.g.…”
Section: Associations Between Polymorphisms Of Disease Pathogenesis Psupporting
confidence: 69%
“…For example, studies of cholesterol-lowering drugs, the hydroxymethylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, conducted in fairly large populations with specific clinical endpoints (beyond lipid changes), have focused on genetic polymorphisms in proteins not directly involved in the pharmacologic mechanism of the drug, namely apolipoprotein E (APOE), cholesteryl ester transfer protein (CETP), stromelysin-1 and β-fibrinogen. [64][65][66]68,69,72] These studies and their results have been strikingly consistent. Firstly, they investigated a genetic polymorphism thought or documented to be associated with an adverse clinical outcome (e.g.…”
Section: Associations Between Polymorphisms Of Disease Pathogenesis Psupporting
confidence: 69%
“…1 Therapeutic interventions related to the common apo E genotype. In addition, Nemeth et al (84) observed that the relationship between apo E genotype and gemfibrozil response depends on the type of hyperlipoproteinemia under scrutiny. Both primary and familial hypercholesterolemia, diabetes, and postmenopausal syndrome have been investigated.…”
Section: Involvement Of Apo E In Drugs and Dietary Responsesmentioning
confidence: 99%
“…The outcome literature with HMG CoA-reductase inhibitors (statins) are particularly interesting in this regard. Studies of the statins that were conducted in fairly large populations with induced dyskinesias specific clinical endpoints (beyond lipid changes) have focused on the polymorphic genes coding the following proteins: apolipoprotein E, cholesteryl ester transfer protein (CETP), stromelysin-1, and β-fibrinogen (28,29,49,81,110,114). These studies and their results have been strikingly consistent.…”
Section: Drug Target Pharmacogenetics and Pharmacogenomicsmentioning
confidence: 92%